Capping the tenure of CEOs as a Good Corporate Governance Strategy: Prospects and Challenges - Paradzai Munyede (Journal of Contemporary Governance and Public Policy, 2021)
The concept of good corporate governance has gaining traction over the last three decades in the private and public sectors as a response to serious financial scandals and maladministration practices in organisations around the globe. Antidotes provided in previous studies on these corporate failures attributed this to poor board compositions and inadequate separation of power. Whilst this was part of the problem, little effort was put to understand how Chief Executive Officers (CEOs) term limits could also contribute to good governance practice which would make organisations avoid scandals. Therefore, the purpose of this paper is to explore how capping CEOs tenure could enhance good corporate governance in the public and private sectors. This paper is based on a qualitative approach and used content analysis to review data from published records like journal articles. This article posited that capped term limit in both the public and private sectors is ideal as it enhances good corporate governance practice which in turn will make institutions effective and responsive to changes in their operating environment.